Cell therapy with intravascular administration of mesenchymal stromal cells continues to appear safe: An updated systematic review and meta-analysis. (February 2020) - Thompson, Mary; Mei, Shirley H.J.; Wolfe, Dianna; Champagne, Josée; Fergusson, Dean; Stewart, Duncan J.; Sullivan, Katrina J.; Doxtator, Emily; Lalu, Manoj; English, Shane W.; Granton, John; Hutton, Brian; et al.
Abstract: Background: Characterization of the mesenchymal stromal cell (MSC) safety profile is important as this novel therapy continues to be evaluated in clinical trials for various inflammatory conditions. Due to an increase in published randomized controlled trials (RCTs) from 2012–2019, we performed an updated systematic review to further characterize the MSC safety profile. Methods: MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Web of Science (to May 2018) were searched. RCTs that compared intravascular delivery of MSCs to controls in adult populations were included. Pre-specified adverse events were grouped according to: (1) immediate, (2) infection, (3) thrombotic/embolic, and (4) longer-term events (mortality, malignancy). Adverse events were pooled and meta-analyzed by fitting inverse-variance binary random effects models. Primary and secondary clinical efficacy endpoints were summarized descriptively. Findings: 7473 citations were reviewed and 55 studies met inclusion criteria ( n = 2696 patients). MSCs as compared to controls were associated with an increased risk of fever (Relative Risk (RR) = 2·48, 95% Confidence Interval (CI) = 1·27–4·86; I 2 = 0%), but not non-fever acute infusional toxicity, infection, thrombotic/embolic events, death, or malignancy (RR = 1·16, 0·99, 1·14, 0·78, 0·93; 95% CI = 0·70–1·91, 0·81–1·21, 0·67–1·95, 0·65–0·94, 0·60–1·45; I 2 = 0%, 0%, 0%, 0%, 0%). No included trials were ended prematurely due to safety concerns. Interpretations: MSC therapy continues to exhibit a favourable safety profile. Future trials should continue to strengthen study rigor, reporting of MSC characterization, and adverse events. Funding: Stem Cell Network, Ontario Institute for Regenerative Medicine and Ontario Research Fund